Analysis of the Impact of Covid-19 in Triggering Spouse Conflict Leading to Divorce - Turuki, Zulfikar; Junus, Nirwan; Sarson, Mohamad Taufiq Zulfikar (Universitas Negeri Gorontalo, 2023)
This research aims to analyze the impact of Covid-19 in triggering spousal conflict that leads to divorce. This research uses a normative-empirical legal research method (applied law research) which is basically a combination of normative legal approaches with the addition of various empirical elements. The results obtained from this research are that there are several impacts of Covid-19 which are factors in the occurrence of divorce between couples based on data from the Gorontalo City Statistics Agency, not a few divorce rates during the Covid-19 period, one of the biggest factors is economic factors that affect everyone in this world.